Making a living from your eBay business - Miller, Michael, 1958- (Que, 2006)
The power of online auctions is attracting hundreds of thousands--if not millions--of users who want to turn their eBay hobbies into profitable businesses. While turning an eBay hobby into an eBay business might look easy, making that business profitable is much more difficult. Not enough sellers treat their eBay sales as a business, and subsequently are disappointed in the results. To launch a successful and profitable eBay business, the detailed instructions in this book will show you how to get started. It will help you determine what kind of business you want to run, write an action-oriented business plan, establish an effective accounting system, set up a home office, obtain starting inventory, arrange initial funding, establish an eBay presence, and arrange for automated post-auction management. This book is a step-by-step guide for anyone serious about making money from their eBay sales. Unlike other computer-oriented titles, this is a straight-ahead business book that shows how to set up and run different types of eBay businesses, and how to maximize sales and profits while doing so. This book includes a section titled "Choosing Your eBay Business" that details six different types of eBay businesses you can start. Included in this section is a chapter on eBay Trading Assistants (AKA drop-off stores or consignment stores), which is the newest form of an eBay business.